Prognostic factors for metastasis in cutaneous melanoma - Ana Carolina Figueiredo Pereira Cherobin; Alberto Julius Alves Wainstein; Enrico Antônio Colosimo; Eugênio Marcos Andrade Goulart; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Melanoma is a malignant neoplasia that shows high mortality when diagnosed in advanced stages. Early identification of high-risk patients for the development of melanoma metastases is the main strategy to reduce mortality. Objective: To assess the influence of eight epidemiological and histopathologic features on the development of metastases in patients diagnosed with primary cutaneous melanoma. Methods: Our historical cohort comprised patients with invasive primary cutaneous melanoma seen between 1995 and 2012 at a public university hospital and a private oncologic surgery institution in Southeastern Brazil. The following variables were analyzed: gender, age, family history of melanoma, site of the primary tumor, clinical and histologic subtype, Breslow thickness, histologic ulceration and the mitotic index. Kaplan-Meier univariate test and multivariate Cox proportional hazard analysis were used to assess factors associated with disease-free survival. Results: Five hundred and fourteen patients were enrolled. The univariate analysis identified the following significant risk factors: gender, age, site of the tumor, clinical and histologic subtype, Breslow thickness, histologic ulceration and mitotic index. Multivariate analysis included 244 patients and detected four significant prognostic factors: male gender, nodular clinical and histologic subtype, Breslow thickness > 4mm, and histologic ulceration. The mitotic index was not included in this analysis. Study limitations: Small number of patients in multivariate analysis. Conclusions: The following prognostic factors to the development of melanoma metastasis were identified in the study: male gender, nodular histologic subtype, Breslow thickness > 4mm and ulceration.